PRINSIP NASIONALISME DALAM LIRIK LAGU KEBANGSAAN ARAB SAUDI DAN LAGU KEBANGSAAN INDONESIA - Fharis Romanda (An-Nahdah Al-'Arabiyah is published by Department of Arabic Language and Literature in cooperation with The Center for Research and Community Service (LP2M), 2022)
This study aims to describe the construction of the principle of nationalism in two different national anthems, namely the national anthem of Saudi Arabia and the national anthem of Indonesia. This study will compare the lyrics of the Saudi Arabian national anthem and the first verse of the song “Indonesia Raya” which is the Indonesian national anthem based on Hertz's principle of nationalism. This study uses comparative literature theory, which is to compare literary works from two different countries, different languages, and also different cultures. This study resulted in differences and similarities between two literary works in the form of poetry or lyrics of the national anthem of two countries, namely Saudi Arabia and Indonesia. The national anthem of Saudi Arabia by Ibrahim Khafaji represents the principle of nationalism which is integrated with Islamic values. The principle of nationalism in the Indonesian national anthem or known as the song